GEODERIV: EVALUATING THE PRACTICALITY AND EFFECTIVENESS OF AN INTERACTIVE GEOGEBRA-BASED MEDIA FOR DERIVATIVE CONCEPTS IN SENIOR HIGH SCHOOL STUDENTS - Hafis; I Ketut Suastika; Rahaju (IAIN Ambon, 2026)
Derivative concepts are often difficult for students because they involve abstract relationships between symbolic procedures and graphical representations. This study aimed to evaluate the practicality and effectiveness of GeoDeriv, an integrated GeoGebra-based learning media designed to support twelfth-grade senior high school students in learning derivative concepts. The study was conducted within a research and development project using the ADDIE model, with this article specifically reporting the evaluation stage through field testing. The participants were 31 twelfth-grade students at MA YMPI Rappang. GeoDeriv integrates derivative materials, interactive simulations, graphical visualizations, practice tasks, and solution displays within a single GeoGebra-based learning environment to support students’ conceptual understanding and visual reasoning. Data were collected through student and teacher response questionnaires, a student learning outcomes test, and classroom activity observations. The results showed that GeoDeriv was highly practical, with practicality scores of 94.00% from students and 93.75% from the teacher. Its effectiveness was supported by the One-Sample Wilcoxon Signed-Rank Test (p < 0.05), indicating that students’ post-test scores differed significantly from the Minimum Mastery Criterion. Student activity reached 90.00%, which was categorized as very good. These findings indicate that GeoDeriv provides promising classroom-level support for derivative learning by facilitating students’ engagement with symbolic, graphical, and conceptual representations in an integrated digital learning environment. Keywords: Derivatives; Interactive Mathematics Learning Media; GeoGebra